Resistance and induction of viable but non culturable states (VBNC) during inactivation of E. coli and Klebsiella pneumoniae by addition of H2O2 to natural well water under simulated solar irradiation. (1st January 2021) - Alvear-Daza, John J.; García-Barco, Alejandra; Osorio-Vargas, Paula; Gutiérrez-Zapata, Héctor M.; Sanabria, Janeth; Rengifo-Herrera, Julián A.
Highlights: Solar/H2 O2 processes in well waters induced VBNC states in both bacteria strain. E. coli was the only bacteria whose viability was completed reduced. Post-irradiation effects were found through viability measurements. Bacteria underwent size reduction and shape changes during the solar treatment. K. pneumoniae exhibited high resistance to the treatment following its viability. Abstract: Inactivation of E. coli and Klebsiella pneumoniae by addition of H2 O2 10 mg L −1 into natural well water samples containing natural total iron concentrations (around 0.3 mg L −1 ) under simulated solar light was followed by bacterial culturability (plate count) and viability (DVC-FISH). Results showed that culturability of both bacteria was totally reduced while viability was only completely depleted for E. coli in well water samples depending of total iron concentration. Post-irradiation effects in presence of residual H2 O2 showed that viability of both bacteria kept dropping being totally reduced for E. coli cells while K. pneumoniae decreased only 1-log. SEM micrographs showed that E. coli and K. pneumoniae cells underwent morphological changes and size reduction according to VBNC states. Different dark and photo-induced processes where physical-chemical features of groundwater samples play an important role could be responsible of bacteria abatement. Graphical abstract: Image, graphical abstract